2020
DOI: 10.1002/ajmg.a.62012
|View full text |Cite
|
Sign up to set email alerts
|

Severe course with lethal hepatocellular injury and skeletal muscular dysgenesis in a neonate with infantile liver failure syndrome type 1 caused by novel LARS1 mutations

Abstract: Infantile liver failure syndrome type 1 (ILFS1) is a recently recognized autosomal recessive disorder caused by deleterious mutations in the leucyl‐tRNA synthetase 1 gene (LARS1). The LARS1 enzyme is responsible for incorporation of the amino acid leucine during protein polypeptide synthesis. Individuals with LARS1 mutations typically show liver failure from infancy to early childhood during periods of illness or other physiological stress. While 25 patients from 15 families with ILFS1 have been reported in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…To obtain more efficient knock-in using genome editing, we replaced the two bases that changed the PAM sequence (Fig 3A). Among the pathogenic variants in the LARS gene (p.W201G/p.I451F) identified in our patient, we focused on the p.I451F variant, as it has been found in other Japanese patients, suggesting a Japanese founder effect, and is located within the editing domain of the LARS protein, where pathological variants have accumulated [30]. We designed a model of the larsb I451F mutation ( larsb-I451F ) to elucidate the pathogenesis of ILFS1 (Fig 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain more efficient knock-in using genome editing, we replaced the two bases that changed the PAM sequence (Fig 3A). Among the pathogenic variants in the LARS gene (p.W201G/p.I451F) identified in our patient, we focused on the p.I451F variant, as it has been found in other Japanese patients, suggesting a Japanese founder effect, and is located within the editing domain of the LARS protein, where pathological variants have accumulated [30]. We designed a model of the larsb I451F mutation ( larsb-I451F ) to elucidate the pathogenesis of ILFS1 (Fig 3B).…”
Section: Resultsmentioning
confidence: 99%
“…An in silico analysis suggested that W201G probably damaged the protein structure and/or function (Polyphen2: score 1.000; probably damaging [http://genetics.bwh.harvard.edu/pph2/]) (S1 Table ). Another missense variant, c.1351A>T; p.I451F in exon 14 [NM_020117.9], was maternally inherited and had been previously described in a Japanese patient with ILFS1 [30]. It is located in the LARS editing domain (Fig 2A).…”
Section: Lars1 As a Single Candidate Gene By Wesmentioning
confidence: 99%
“…Our review of the literature identified 14 articles, 7 on LARS1 mutations and 7 on MARS1 mutations, such that including our 3 patients, 65 patients with LARS1 or MARS1 mutations (respectively 27 and 38) have so far been described in the literature. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Twenty-one of these patients (32.3%) patients died: 6/27 of the patients with LARS1 mutations (4 boys and 2 girls) and 15/38 of the patients with MARS1 mutations (11 boys and 4 girls). One of the patients with a LARS1 mutation underwent liver transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory abnormalities are indeed far more frequent in patients with MARS1 mutations and precise diagnoses as alveolar proteinosis or interstitial pulmonary disease are well described. However, most recent reports of LARS1 mutations (1,8,14) also describe associated respiratory abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple single amino acid changes in EPRS1, LARS1, DARS1, IARS1, and MARS1 have been reported but MSC localization and their potential roles in cancer remain to be explored [170] , [171] , [172] , [173] . Interestingly, several mutations in DARS1 (Arg460His, Pro464Leu) that cause hypomyelination with brain stem and spinal cord involvement and leg spasticity were found that might induce release from the MSC [172] .…”
Section: Factors Determining Constituent Release From the Mscmentioning
confidence: 99%